Monitoring the activity of gamma radiation on biosorption of heavy metals by some fungi - Menna Allah Ashraf Youssef Sayed; Khaled Fawzy Elyasergy; Moustafa Abdelsalam Aly; Tahany Mohamed Ali Abdelrahman (Cairo : Menna Allah Ashraf Youssef Sayed, 2021)
Among the different types of microorganisms; the fungal biomass is considered to be an effective mediator for bioremediation of heavy metals due to their higher surface area and extensive hyphal density in the soil. In the present study, an isolate of A. japonicus was isolated from soil of Middle Eastern Regional Radioisotope Center for the Arab Countries (MERRCAC). Soil analysis revealed that Zinc ,Cadmium and Lead concentration were 185, 60 and 5.25 mg/l, respectively. The aim of the present study was to monitor the effect of gamma irradiation with (50-250 Gy) doses on the removal efficacy of heavy metals from soil by A. Japonicus . It was indicated that combined treatments of A. japonicus with gamma irradiation doses displayed an enhancement on biosorption capacity and dry biomass gain than single treatment. It was found that citric acid production by A. japonicus was affected by both gamma irradiation dose and type of heavy metal treatment. In addition the oxalic acid production by A. japonicus was decreased in case of Cd, Pb but increased in the case of Zn treatment. Fourier Transform Infrared Spectroscopic (FTIR) analysis showed that the fungal biomass possesses in its surface for treated and control hydroxyl, carboxyl and amine groups, some treatments were accompanied by shift or disappearance of some surface groups. On the other hand, Transmission electron microscope (TEM) examination of the irradiated A. japonicus cells demonstrated an accumulation of heavy metals particles on the fungal cell wall surface and within the cells, this indicate that heavy metal accumulation by fungi occurs by two methods absorption inside the cell and adsorption on the cell wall.The current study expressed a potential new method for enhancing microbial biosorption capacity of heavy metals using low doses of gamma radiation
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany and Microbiology
Issued also as CD
Keywords: Aspergillus japonicus; Fungi; Gamma Radiation